Model Approach to Development Human Resources in Higher Education - Muflihin, Muh. Hizbul (International Conference of Moslem Society, 2019)
Human Resource management is necessary for higher education institutions, because it is seen to enhance the achievement of the objectives of institutional effectiveness. To reach this objective, the study of human resources management by an educational institution to be very important, because it will be able to show how educational institutions should acquire, develop, use, evaluate, and maintain employee quantitatively and qualitatively. Development of human resources is sensed as to the personal empowerment of employees. Empowerment is done with the intention that potential, abilities and basic skills possessed by employees can be enhanced or may be used as an effort to shore up the smooth implementation of activities. In the concept of human resource development are two sides of profits, personal first employees to be more professional, well-trained and able to act decisively and quickly. On the organizational side of human resource development brings the advantage of implementation of the well, as supported by HR that has been professionally trained, and can reduce costs for training and further education. From a number of management functions are initiated by management experts, the main component of management are considered capable of facing future challenges universities as academic institutions include "planning, resource management, and assessment of results" These three major components will proceed in determining the shape of each cycle which one another at every stage of management. With the assessment of the results, will be able to describe the performance of college management. Performance evaluation then became the basis for planning the next stage of management, therefore, the planning process is dynamic (dynamic planning) and not static. Planning compiled based on performance evaluation to be a reference in designing the resource management within a few years. Overall management process should be conducted in a professional, effective and efficient in order to create good governance colleges. In the PP. No. 66 of 2010 stated that the management of the education unit is based on the following principles: Nonprofit, Accountability, Guarantor of quality, transparency and equitable access. While the model of development of human resources management approach is: a model of clerical, legal, financial, managerial and humanistic models. Human Resouce Development practices, employee performance results will look better and increase if the principles of human resource management universities applied in practice management and delivery of higher education. As the cornerstone of the general implementation of human resource development of quality higher education is to use humanistic approach. Because the use of humanistic approach, will be able to balance the provision of education between clerical and financial concepts.